Pengaruh Daya Tarik Wisata Terhadap Minat Berkunjung Wisatawan Di Kawasan Pecinan Glodok Jakarta Barat Sebagai Wisata Sejarah Dan Budaya - Alfandy, Meidy; Rizki Krisnadi, Antonius (Jurnal Syntax Fusion, 2023)
Tourism is the second largest and most powerful sector in a world economic development. Indonesia is one of the developing countries in the tourism industry and has various natural and cultural beauties. Indonesia has many choices of tourist destinations, one of which is the Glodok Chinatown. The Glodok Chinatown area was once an isolation area for the Chinese ethnic community and at the same time became an economic center which has now become a tourist area with historical & cultural tourism potential. The purpose of this study was to find out whether there is an influence of tourist attraction in the Glodok Chinatown area on the interest of visiting tourists as historical & cultural tourism. This study used a total sample of 100 respondents. This study uses an instrument test consisting of validity and reliability tests. Then there is a classic assumption test which consists of a normality test and a heteroscedasticity test. Then there is a simple linear regression test and a hypothesis test which consists of a T test and the coefficient of determination. The results of the study show that tourist attraction has an influence on tourists' interest in visiting as historical & cultural tourism in the Glodok Chinatown area.